Posterior Lubrication in a patient Urinary retention e.c. suspect urethral stones - Denny Krisna Purnama; Wahyu Hari Santoyo (Jurnal llmu Bedah Indonesia, 2022)
Urinary tract stones (BSK) are the most common disease in urology. In developing countries like Indonesia, the BSK rate continues to increase. Urethral stones are rare cases, the incidence is less than 1% of all cases of urinary tract stones. Urethral stones are one of the causes of acute urinary retention. Urinary retention is an emergency in the field of urology and cases are often encountered in the emergency department that requires immediate action. The management of all types of retention aims to decompress the bladder and reduce the cause of retention by inserting a catheter. This paper discusses cases of urinary retention and causes of urethral stones that have failed to be implanted with a catheter so that posterior lubrication is performed. Keyword: Urethral Stone, Posterior Lubrication